CLASSROOM INTERACTION IN THE ENGLISH SUBJECT FOR THE TENTH GRADE OF SMA N 1 SALAK PAKPAK BHARAT - Dirgahayu Tumangger; Busmin Gurning; Muhammad Natsir (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2018)
This study aimed at finding out the categories of teacher and students talk and the percentage of teacher and students talk during classroom interaction. This study was conducted by using descriptive qualitativedesign. The subjects of this study were the tenth grade students of SMAN 1 Salak and the English teacher who taught at that class in 2017/2018 academic year. The data were the utterances of both teacher and students during the classroom interaction process which were collected by using observation and recorded by using smartphone and recorded it about three meetings.The data collected were analyzed by using Flanders Analysis formulate. The findings of the study showed  Analysis showed, there are ten categories of students and teachers talk that could be found during the classroom interaction and the percentage of each of category was: 2,05% for accepting feeling, 5.88% for praising and encouraging, 5,29% for accepting students’ ideas, 11,17% for asking question, 11,76% for lecturing, 8,52% for giving direction, 14,41% for criticizing, 32,35% for students talk response,6,17% student talk initiation and2,35% for silence and confusion.so the teacher talk percentage was about 60,3% and 38,52% for student. Keywords: classroom interaction, Flanders interaction analysis category system